Aportación de una mirada ecocrítica a los estudios francófonos - Montserrat López Mújica (Çédille: Revista de Estudios Franceses, 2007)
Ecocriticism or ecological literary criticism is slowly making its way into the European academic world. Its followers are con-vinced that, in this era of environmental crisis, Ecocriticism can provide a new look at literary texts and, in a manner, contribute to increasing the respect for the environment, a renewing of our ties with the earth and its inhabitants, and strengthening our relationships with our planet. This article will present the status of this ecocritical view in francophone studies.